Analisis Pengendalian Biaya Dan Waktu Pada Proyek Pembangunan Manado Outer Ring Road III Tahap 1 - Delfini Maria Mona; Sudenroy Mentang; Novriana Amelia Pangemanan (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
In a construction project, there are often delays in the completion of project activities that exceed the predetermined time, therefore, good cost and time control is expected to assist the implementation of the project as planned. There are several methods that can be used for cost and time management, one of which and the subject of discussion is the Earned Value Analysis method. Result Value Analysis is used with the aim of being able to forecast (forecasting) the extent to which the project implemented is in accordance with the work plan. The earned value concept, which integrates time and cost aspects, allows construction contractors to use it as an appraisal material to estimate costs and turnaround times, as it allows them to verify the performance the project has received over time. The Manado Outer Ring Road III Phase 1 construction project is a construction scheduled to be completed within 43 weeks with a contract value of Rp. 47,621,085.000,00. From the research results, the estimated total cost of the work until the end of the project is Rp. 42,286.724,876.09 with a cost index > 1, indicating that the project realization costs were smaller than the budgeted ones. It can be concluded that the Manado Outer Ring Road III Phase 1 project experienced a delay in implementation time but did not cause cost deviations. Keywords : Cost and Time, Earned Value Analysis, Labor Productivity